Mechanisms of financing investment projects by modern commercial banks - Abdurashidova M.K.; Karimova A.M (THE INNOVATION ECONOMY, 2026)
The article examines the mechanisms of financing investment projects by modern commercial banks, focusing on their structural features, operational principles, and practical efficiency. The study analyzes the dynamics of investment lending, risk assessment methods, financing instruments, and project monitoring systems. The findings indicate that although investment activity in the banking sector is expanding, several systemic issues remain, including lengthy expertise procedures, insufficient digitalization, and limited use of project finance models. The article provides scientific and practical recommendations for improving investment financing mechanisms.